(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2006)
It’s provided the analysis results for the dielectric Resonators electromagnetic parameters with low permittivity dielectric in the optical and infrared wave-length ranges. The frequencies and Q-factors of the spherical two-layer dielectric resonators is tested. It’s studied resonances of very big number coupling spherical resonators. An existence of high-Q resonances is demonstrated